Association between mink coronavirus (MCoV), Campylobacter spp., and diarrhea in farmed mink (Neogale vison) - Michelle Lauge Quaade; Mikael Leijon; Mikhayil Hakhverdyan; Thomas Bruun Rasmussen; Charlotte Kristiane Hjulsager; Lars Andresen; Karin Mundbjerg; Anne Sofie Vedsted Hammer (PLoS ONE, 2026)
Diarrhea outbreaks significantly affect the health and growth of farmed mink, posing economic and welfare challenges. While various pathogens have been linked to mink diarrhea, the causes during the weaning period remain unclear. Sporadic associations of mink coronavirus (MCoV), Campylobacter , and gastrointestinal disease in mink have been suggested. This study investigates the occurrence and levels of MCoV and Campylobacter in fecal samples from Danish farm mink ( Neogale vison ) and their potential association with post-weaning anorexia diarrhea syndrome (PADS), growth-period diarrhea (GPD), or pre-weaning diarrhea (PWD). The focus of the study is on PADS, studied through two case-control setups where case farms had known problems with PADS and control farms without such problems. Animals were also diagnosed based on necropsy pathological findings. Seventeen MCoV genomes were determined from five Danish farms. This data facilitated the development of an MCoV RT-qPCR and was applied across three study groups. Results showed high prevalence of both MCoV and Campylobacter spp. in all groups. No link was found between MCoV presence or levels and PADS diagnosis on the individual level; however, farm-level analysis revealed that MCoV was 2.35 times more likely (95% CI 1.027; 5.056) on PADS case farms than controls. Mink with PWD exhibited higher MCoV levels compared to GPD cases, suggesting a role at this developmental stage. Phylogenetic analysis revealed diverse and farm-specific MCoV strains, with sequences from healthy controls forming a distinct subclade, hinting at strain-specific pathogenicity. Campylobacter spp. presence was not significantly associated with PADS, but higher levels were observed in mink with PADS versus those without (not tested for PWD). These findings highlight the importance of surveillance and rigorous hygiene practices on mink farms to address risks from MCoV and Campylobacter spp., calling for further research to clarify their roles in PADS and overall mink health.